IMPLEMENTASI MANAJEMEN STRATEGIK MENGGUNAKAN ANALISIS SWOT SMP MUHAMMADIYAH 17 CIPUTAT - Daffa Al Manfaluthi; Ade Hoerul; Harri Priadi Nugraha (Media Riset Bisnis Manajemen Akuntansi, 2026)
This study aims to analyze the implementation of strategic management through SWOT analysis at SMP Muhammadiyah 17 Ciputat. Strategic management is a systematic approach that integrates various management aspects to make strategic decisions effectively and efficiently. SWOT analysis serves as an essential tool to evaluate internal factors (strengths and weaknesses) and external factors (opportunities and threats) in formulating effective strategies. This research employed a qualitative descriptive method through field observations, in-depth interviews, and discussions with school officials conducted on October 30, 2025. The findings reveal that the school's main strength lies in its character development program and faith-building (IMTAQ) initiatives. However, challenges include declining student enrollment post-COVID-19, inadequate science laboratory management, and insufficient guidance counselors. Opportunities exist through tahfidz programs that can provide scholarship access, while threats emerge from competition with public schools employing unofficial admission practices. This study demonstrates that SWOT analysis-based strategic management is effective for evaluating and formulating school development strategies.Keywords : Strategic Management, SWOT analysis, school development, Islamic education, competitive advantage.